Reading Eagle, Pa., reviewer Tony Lucia column: TV and art films - reviewer Tony Lucia (Knight Ridder Tribune Business News, 2006)
Millennium Mambo (2001). Few contemporary filmmakers are as venerated by critics as the Chinese-born, Taiwan-based director Hou Hsiao-hsien. Hou's painstakingly composed films -- often set in the past, and assembled from lengthy, meditative shots that often double as complete scenes -- tend to be antithetical to Hollywood style. So despite the critical raves, few of his movies, which include "The Puppetmaster" (1993) and "Flowers of Shanghai" (1998), are exhibited outside of New York, L.A. and a few other major metropolitan areas, and are almost never seen on TV. But here's an exception. "Millennium Mambo" may not be among Hou's greatest films, perhaps, but it's clearly in a class of its own.